Ulnar collateral ligament tear in elite baseball pitchers: Are high school showcase exposures associated with injury? - Kriz, P. K.; Staffa, S. J.; Kriz, J. P.; DeFroda, S. (The American Journal of Sports Medicine, 2022)
Background: Ulnar collateral ligament reconstruction (UCLR) surgeries have increased significantly in amateur and professional baseball pitchers. Although showcase participation has been considered an injury risk factor, limited data are available to corroborate this association.